Arabic vocabulary mastery in early childhood through singing - Meutia Rahmah; ade tursina; nuraisyah (Institut Agama Islam Negeri Langsa, 2021)
As a foreign language, children aged 5-6 years in Langsa are still lacking in mastering Arabic vocabulary. This study aims to describe how the singing method enriches children's Arabic vocabulary. The research applied Classroom Action Research (CAR) design with the Kemmis and Mc. Taggart in two cycles. Each cycle consists of four stages; planning, implementing actions, observing, and reflecting. The research subjects were 6 children in Gampong Geudubang Aceh, Langsa. The result shows that Arabic vocabulary mastery of early childhood through the singing method has increased in each cycle. The first cycle obtained 44.66% on average and the second cycle increased to 80.3% in its average. It can be concluded that the singing method can increase the mastery of Arabic vocabulary for early childhood.